STRENGTHENING TEACHERS’ CAPACITY IN DEVELOPING A CREATIVE QUR’AN LEARNING CENTER THROUGH THE USE OF AUGMENTED REALITY BASED FLASHCARDS - Evi Maulidah (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2025)
Al-Qur'an Education Parks (TPQ) are crucial in producing morally upright Muslims who can read the Qur'an. Nonetheless, traditional approaches that are less appropriate for the traits of the digital generation continue to dominate education at TPQs. TPQ Fathur Rahman in Gumuk Jajar Hamlet, Sumberdanti Village, also suffers from this condition. Its teachers still have limitations when it comes to using technology-based learning materials, even with the potential of individual assets and strong community support. Through the use of Augmented Reality (AR)-based Flashcard Educational Game Tools (APE), this community service project seeks to enhance TPQ teachers' ability to foster creative learning. Through the phases of discovery, dream, design, and define-destiny, the Asset-Based Community Development (ABCD) approach is employed. Mapping community resources, training, and mentoring the use of AR flashcards in education are among the activities. The outcomes of the community service demonstrate that teachers are better able to use AR-based learning materials, students are more motivated and focused, and parents are more involved in helping their kids learn at home.